Peri‐operative administration of tranexamic acid in lower limb arthroplasty: a multicentre, prospective cohort study. (4th June 2020) - Lloyd, T. D.; Neal‐Smith, G.; Fennelly, J.; Claireaux, H.; Bretherton, C.; Carr, A. J.; Murphy, M.; Kendrick, B. J.; Palmer, A. J. R.; ,
Summary: In the UK, tranexamic acid is recommended for all surgical procedures where expected blood loss exceeds 500 ml. However, the optimal dose, route and timing of administration are not known. This study aimed to evaluate current practice of peri‐operative tranexamic acid administration. Patients undergoing primary total hip arthroplasty, total knee arthroplasty or unicompartmental knee arthroplasty during a 2‐week period were eligible for inclusion in this prospective study. The primary outcome was the proportion of patients receiving tranexamic acid in the peri‐operative period. Secondary outcomes included: dose, route and timing of tranexamic acid administration; prevalence of pre‐ and postoperative anaemia; estimated blood loss; and red blood cell transfusion rates. In total, we recruited 1701 patients from 56 NHS hospitals. Out of these, 1523 (89.5%) patients received tranexamic acid and of those, 1052 (69.1%) received a single dose of 1000 mg intravenously either pre‐ or intra‐operatively. Out of the 1701 patients, 571 (33.6%) and 1386 (81.5%) patients were anaemic (haemoglobin < 130 g.l −1 ) in the pre‐ and postoperative period, respectively. Mean (SD) estimated blood loss for all included patients was 792 (453) ml and 54 patients (3.1%) received a red blood cell transfusion postoperatively. The transfusion rate for patients with pre‐operative anaemia was 6.5%, compared with 1.5% in patients without anaemia. Current standard of care in the UK is to administer 1000 mg of tranexamic intravenously either pre‐ or intra‐operatively. Approximately one‐third of patients present for surgery with anaemia, although the overall red blood cell transfusion rate is low. These data provide useful comparators when assessing the efficacy of tranexamic acid and other patient blood management interventions in future studies.